Direk of indirek - 'n antwoord op h. M. Kuitert se siening Van skrifberoep in die etiek - Stoker, H. G. (Koers, 1987)
An analysis is provided of HM Kuitert's view of a call on Scripture in Ethics. This is effected by the author's analysis and synthesis of the view of Kuitert. In Kuitert's view man, together with his capabilities, is considered so highly that man becomes the norm of the moral. This anthropocentric ethics is in conflict with the traditional Refored view, viz. that Ethics should be theocentric. The author concentrates on Kuitert's argumentation in his work Het Schriftberoep in de Ethiek. In this article the view is taken that the Bible is the Word of God and that the authors of the Bible were inspired by the Holy Spirit in an organic manner. It is also argued that Holy Scripture as the Word of God cannot contradict itself, and that the seeming contradictions exist as a result of the sin-induced corruption of the mind of the exegete/hermeneut. In opposition to Kuitert's view, guidelines are offered for Scripturally valid calls on Scripture in Ethics.